2019
DOI: 10.1177/1362361319856974
|View full text |Cite
|
Sign up to set email alerts
|

Adapted cognitive behavior therapy for obsessive–compulsive disorder with co-occurring autism spectrum disorder: A clinical effectiveness study

Abstract: Obsessive–compulsive disorder and autism spectrum disorder commonly co-occur. Adapted cognitive behavior therapy for obsessive–compulsive disorder in adults with autism spectrum disorder has not previously been evaluated outside the United Kingdom. In this study, 19 adults with obsessive–compulsive disorder and autism spectrum disorder were treated using an adapted cognitive behavior therapy protocol that consisted of 20 sessions focused on exposure with response prevention. The primary outcome was the clinici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…QoL) tend to suggest fewer treatment gains in the areas of everyday functioning that may be particularly important to many autistic people and their families (Fletcher-Watson & McConachie, 2015; McConachie et al, 2015). For example, though cognitive behavioural therapy (CBT) is the most widely supported intervention approach for managing anxiety symptoms in autism (Kreslins et al, 2015; Sukhodolsky et al, 2013; White et al, 2018), improvements in QoL following CBT are not consistently identified (Flygare et al, 2020; van Steensel & Bogels, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…QoL) tend to suggest fewer treatment gains in the areas of everyday functioning that may be particularly important to many autistic people and their families (Fletcher-Watson & McConachie, 2015; McConachie et al, 2015). For example, though cognitive behavioural therapy (CBT) is the most widely supported intervention approach for managing anxiety symptoms in autism (Kreslins et al, 2015; Sukhodolsky et al, 2013; White et al, 2018), improvements in QoL following CBT are not consistently identified (Flygare et al, 2020; van Steensel & Bogels, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive behavior therapy (CBT) is recommended as the first-line treatment for OCD ( American Psychiatric Association, 2007 ). When appropriately adapted and delivered by specialist clinicians, CBT can be effective for OCD in autistic individuals ( Kose et al, 2018 ; Flygare et al, 2020 ; Martin et al, 2020 ), though the reported effects are somewhat smaller compared to those reported in non-autistic individuals with OCD ( Murray et al, 2015 ; Jassi et al, 2021 ). For example, in the largest naturalistic study to date, 53% of 172 children with OCD and ASD were classed as treatment responders, compared to nearly 77% of non-autistic children with OCD ( Jassi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 93%
“…It is not always practical to return to the site of the trauma, so imaginal exposure therapy can be used in the therapist’s office. Imaginal exposure therapy, wherein patients are exposed to their own thoughts and mental images, benefitted young people with ASD who had obsessive-compulsive disorder to a lesser degree than typically developing children [ 39 ]. A central part of in vivo and imaginal exposure therapy is homework, where patients are asked to reinforce what they have learned in therapy outside of the clinical setting [ 40 ].…”
Section: Exposure-based Therapies In Asdmentioning
confidence: 99%